INNOVATIONS IN DATA EXCHANGE FOR LAW ENFORCEMENT TASKS - Krutova, Erika (Border Security and Management, 2023)
Information systems are becoming increasingly important in the functioning of law enforcement authorities. In addition to border control in the area, the exchange of information between national competent services is of particular importance. This process is ensured in the European Union through a number of tools, some of which the Schengen Information System, Passenger Name Record, the Europol’s Secure Information Exchange Network Application are. Legal instruments such as the Prüm Decisions and the Swedish Initiative have been adopted to reduce legal barriers and accelerate the exchange of information between national competent services. However, criminal threats force to reassessment of the effectiveness of existing cooperation and for even more targeted action. Although existing resources and technological capabilities allow information to be searched online, to perform cross-checks for match detection and rapid data exchange, modern options have not been fully implemented yet. The aim of this article is to analyse the existing instruments for information exchange and to assess the novelties of the Directive of the European Parliament and of the Council on information exchange between law enforcement authorities of Member States, repealing Council Framework Decision 2006/960/JHA. Empirical research methods were used in the study. The author of the study comes to the conclusion that the implementation of the Directive requires significant improvements in national regulation.